Monitoring and resuscitation of severely ill and shocked patients - Morales Corvacho, Jorge Edmundo (2010)
Shock is the most frequent hemodynamic emergency in clinical practice, and patients lives depend on its timely and adequate management; consequently, it is of outmost importance that physicians should know every basic aspect with respect to the initial management of shock and learn how to use both mechanic and electronic monitoring devices. A brief overview of these topics is presented and we review guidelines related to diagnosis, therapy, and monitoring patients in hemodynamic shock.